CO2 Adsorption Capacities in Zeolites and Layered Double Hydroxide Materials - Megías-Sayago, Cristina; Bingre, Rogéria; Huang, Liang; Lutzweiler, Gaëtan; Wang, Qiang; Louis, Benoît (Frontiers in Chemistry, 2019)
The development of technologies that allow us to reduce CO2 emissions is mandatory in today’s society. In this regard, we present herein a comparative study of CO2 adsorption over three types of materials: zeolites, layered double hydroxides (LDH) and zeolites coated LDH composites. The influence of the zeolite Si/Al ratio on zeolites sorption capacity along with the presence of mesopores was investigated. By comparing these results with the well-known performance of LDHs, we aim to provide insights on the factors that may influence the CO2 capture capacity over zeolites, thus providing useful tools for tuning their properties upon post-treatments.